PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGGUNAAN WORKSHEET BERMUATAN NUMERASI EDUKASI DENGAN MEMANFAATKAN MEDIA GAMBAR BERGERAK DI SDN 3 TOLITOLI - Agustina, Agustina; Ummah BK, Muh. Khaerul; Mustakim, Mustakim (Universitas Batanghari Jambi, 2025)
Mathematics learning problems are caused by students' disinterest in the subject, which affects learning outcomes. For this reason, interesting learning materials must be provided. The aim of this research is to improve mathematics learning outcomes through the use of worksheets which contain learning to count using moving image media. Classroom action research (PTK) This research consists of two cycles which include planning, implementation, observation and reflection at the action implementation stage. Students' understanding of the material and learning outcomes can be improved by carrying out learning actions through the use of educational numeracy-based worksheets with moving image media. Apart from that, students' interest in mathematics subjects can be increased by using interesting learning media and worksheets based on numeracy education that involve students directly in group interactions.